(untitled) (Progressive Agriculture, 2013)
The experiment was carried out under three treatments each with two replications. Fish population density was 80 fish per decimal (silver carp 32, tilapia 32 and mrigal 16) under treatment-1, 120 fish per decimal (silver carp 48, tilapia 48 and mrigal 24) under treatment-2 and 160 fish per decimal (silver carp 64, tilapia 64 and mrigal 32) under treatment-3. The average initial length and weight of the fingerlings of silver carp, tilapia and mrigal were 7.49, 5.12, and 5.56 cm and 8.00, 2.00 and 1.50 g respectively. The ponds were fertilized fortnightly with cowdung, urea and TSP (triple super phosphate) at the rates of 5 kg, 60 g, and 90 g per decimal, respectively. During the experimental period, the range of water temperature (30.20 to 32.90°C), transparency (28 to 38 cm), dissolved oxygen (8.20 to 10.60 mg/L), pH (6.90 to 7.90), total alkalinity (92.00 to 127.00 mg/L), free CO2 (1.00 to 1.60 mg/L), phosphate-phosphorus (1.00 to 1.90 mg/L), and nitrate-nitrogen (1.90 to 3.90 mg/L) were within the productive range and more or less similar in all the ponds under three treatments. There were 25 genera of phytoplankton under five major groups and 10 genera of zooplankton under three major groups in the experimental ponds. The calculated net fish production of the ponds under treatment-1 was 2.62 ton/ha/yr and that of the ponds under treatment-2 was 4.42 ton/ha/yr and that of the ponds under treatment-3 was 5.18 ton/ha/yr. The net fish production under treatment-2 and treatment -3 were 195.58% and 229.20% higher than that of treatment-1, taking net fish production under treatment-1 for 100%. According to profit-cost analysis the ratios of net profit and total cost under treatments 1, 2, and 3 were 1:0.25, 1:0.45, and 1:0.44. According to growth and production treatment-3 is the best, and according to the profit-cost analysis, treatment-2 (ratio 1:0.45) is the best but it is almost same to that of treatment-3. So, the population density of 160 fish per decimal (under treatment-3) might be considered best. It seems that proper determination of stocking density of different fishes in polyculture is very important to increase fish production. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16566 Progress. Agric. 23(1 & 2): 63 73, 2012